Introspecting Translation Of Business Idioms Corpus-based Analysis Of Business Idioms Translation From English Into Arabic - Safia, SEDDIKI; Yasmine, KELLOU (جامعة الوادي - University of Eloued, 2021)
One of the most challenging issues in the realm of translation is translating idioms. This study shall review the main problems encountered when dealing with the translation of business idioms and the extent to which idiomaticity in economic texts is retained, distorted or lost; and why? In addition to discussing possible strategies to keep losses to a minimum. The research shall adopt a corpus-based analysis to highlight that literal translation is not valid with idioms, however, in economic texts, it may be the only solution for the translator to convey idiomaticity with respect to the characteristics of economic discourse.
مقال
Keywords: idiomatic expressions ; translation ; business discourse ; business idioms ; idiomaticity